Analysis of Flexural Stress in Prototype Carding Machine Spindle Gears Made of Aisi 1020 Steel - Muhammad Safii; Khaqurokhim; Rouf Muhammad; Suheri Suheri; Agung Nugroho; Susanto; Muhammad Iqbal Farhan Putra Arya (Fakultas Teknik Universitas Samudra, 2024)
Stress in a mechanically loaded structure is a critical aspect that warrants thorough investigation. The impact of stress on a structure can lead to various consequences, including crack propagation and fracture. Gears play a crucial role in transmitting power and rotation between shafts, making an in-depth analysis of stress in gears essential for ensuring mechanical reliability. Previous research has predominantly focused on stress and loads in gears, utilizing mathematical and numerical methods to explore variations in parameters such as gear diameter and thickness in various vehicles and machines. However, there is a noticeable gap in the literature regarding the analysis of the effect of AISI 1020 steel material on spur gears, particularly in the context of a carding machine for silk processing. This study aims to fill this void by employing a mathematical approach to determine the flexural stress in prototype spindle gears used in a carding machine for silk processing. Through thorough analysis and mathematical calculations, the flexural stress in the prototype spindle gears of the carding machine for silk processing was determined to be 176.32 kg/mm². This research provides valuable insights into the mechanical behavior of gears under load, specifically in the context of the unique requirements of a carding machine for silk processing.